Carbon Monoxide Releasing Molecules - towards a novel antimicrobial therapeutic drug - Mendes, Ana Sofia Soares (2022)
"Carbon monoxide releasing molecules (CORMs) are carbonyl organometallic complexes that liberate controlled amounts of carbon monoxide, which is a signalling and cytoprotective molecule important in human physiology and pathophysiology. Several studies in animals have shown that CORMs are beneficial in the treatment of cardiovascular diseases, inflammation and organ protection. Additionally, CORMs present antimicrobial properties. (...)"